(untitled) (Proceedings of Southern Federal University. Philology, 2018)
Olga M. Kalmukhambetova (Rostov-on-Don, Russian Federation) By now, postmodernism has lost its novelty, but its poetics continue to be studied by domestic and foreign researchers. Active processes of the syntax of the Russian language show that the postmodern worldview influences its development, and allow us to speak of language as a participant in the creation of a new culture. The article is devoted to the current state of the problem of parcellation as a multifaceted phenomenon, as a vivid reception of the actualizing syntax. Key words: postmodernism, parceling, parceled construction, parcel, text.